On the Error Estimate of Nonconforming Finite Element Approximation to the Obstacle Problem (Journal of Computational Mathematics, 2003)
This paper is devoted to analysis of the nonconforming element approximation to the obstacle problem, and improvement and correction of the results in [11], [12].
Keywords: Obstacle problem; Nonconforming finite element.